The multigenerational legacy of diabetes, stigma, disclosure, and anxiety during insulin regimen initiation - Melissa Scollan-Koliopoulos (International Diabetes Nursing, 2026)
Background: Diabetes is a hereditary condition often affecting multiple generations. Preconceived notions of diabetes, its self-management, and consequences are passed down generationally. Stigma formation may occur in families with family members sharing the same internalized or externalized stigma experiences. Stigma is an established mediator of anxiety. Methods: A diverse sample of hospitalized adults (n = 92) with diabetes in the United States of America who were being initiated onto insulin and had a family history of diabetes were administered paper-and-pencil surveys to ascertain their stigma perceptions, disclosure behavior, and anxiety. Regression analyses were used to estimate the effects of family stigma on one’s own stigma and anxiety levels. Results: Recollections of insulin shots by family members and stigma perceptions by the family member significantly predict one’s own internalized stigma of diabetes, explaining 47% of the variance in stigma. Family stigma of insulin significantly explained 35% of the variance in one’s co-occurring internalized stigma, which also significantly explained 94% of the variance in disclosure. Internalized stigma due to diabetes was associated with higher levels of anxiety, significantly explaining 33% of the variance in anxiety. Conclusion: In the context of a multigenerational legacy of diabetes, anxiety may be a consequence of stigma that has been passed down generationally. When family members have a stigma of insulin, along with frequent, strong, vivid, and intrusive memories of their family member using insulin, they are likely to develop a stigma of diabetes themselves. Stigma is a predictor of anxiety. Nurses can tailor psychoeducation interventions that include coping with diabetes and insulin stigma across generations.